Quantum Cloud Computing: Transforming Cryptography, Machine Learning, and Drug Discovery (International Journal of Engineering and Computer Science, 2023)
Quantum Cloud Computing is poised to revolutionize various domains by leveraging the principles of quantum mechanics to enhance computational capabilities beyond classical limits. This paper explores the transformative potential of quantum cloud technologies in three critical areas: cryptography, machine learning, and drug discovery. In cryptography, quantum cloud computing enables the development of unbreakable encryption methods through quantum key distribution and post-quantum cryptographic algorithms, ensuring data security in an increasingly interconnected world. In machine learning, quantum algorithms can significantly accelerate data processing and pattern recognition, opening new avenues for complex problem-solving and predictive analytics. Additionally, the application of quantum computing in drug discovery can streamline molecular simulations and optimize drug design processes, leading to faster identification of viable pharmaceutical candidates. By integrating quantum computing with cloud infrastructure, we can democratize access to advanced computational resources, fostering innovation and collaboration across disciplines. This paper discusses the current state of research, potential applications, and the challenges that lie ahead in harnessing quantum cloud computing to drive advancements in these critical fields.